At which temperature do the deleterious effects of ambient heat "kick-in" to affect all-cause mortality? An exploration of this threshold from an eastern Indian city. Issue 2 (3rd March 2020) - Dutta, Ambarish; Bhattacharya, Shreeporna; AK, Kavitha; Pati, Sanghamitra; Swain, Subhashisa; Nanda, Lipika
ABSTRACT: Despite experiencing hot weathers, limited studies from India explored relationships between ambient heat and health. We studied associations between heat and all-cause mortality to estimate heat threshold(s) affecting health, and examine other affecting dimensions. We conducted time-series analysis with daily maximum temperature and all-cause mortality data of Bhubaneswar city (March–July, 2007–2017), and explored their interactions. Mortality risks rose when daily maximum temperatures were >36.2°C (lower threshold), and even more when >40.5°C (upper threshold). Every degree above36.2°C increased the mortality risk by 2% (mortality rate ratio: 1.02; 95% CI 1.01, 1.03). The effects of maximum temperature increased on days when minimum temperatures were >25.6°C (median). The effect of heat was immediate and lasted for 0–1 day with no lagged effect. Two temperature thresholds with varying mortality risks provided an opportunity for a graded heat warning system. The accentuation of the deleterious effects of heat by the higher minimum temperature calls for its inclusion in the heat warning system in future.